Identifikasi Level Kognitif pada Soal Ujian Akhir Semester Gasal Kelas IV Sekolah Dasar - Erfan, Muhammad; Nurwahidah; Anar, Ashar Pajarungi; Maulyda, Mohammad Archi (Jurnal Kiprah, 2020)
Developing measurement tools in the form of a question is a skill that must be mastered by educators and prospective educators. With the implementation of the 2013 curriculum, educators must not only be able to develop authentic assessments but questions that developed must also be able to encourage students to master lower-order thinking skills (LOTS) as well as higher-order thinking skills (HOTS). This study aims to determine the cognitive level of final semester exam questions at fourth-grade elementary school level on theme 3, theme 4, and theme 5. This study uses descriptive-analytical methods in which the researcher tries to describe the object (question item). The results obtained that most of the multiple-choice questions both in Theme 3, Theme 4, and Theme 5 at the elementary school level grade IV (four) at Gugus 2 Aik Dareq sub-district, Central Lombok are still at the cognitive level of low-level thinking ability (LOTS).